Can information about local government performance induce civic participation? - Joseph J. Capuno; Maria Melody S. Garcia (University of the Philippines, School of Economics (UPSE), 2008)
The question of whether people are motivated to engage in civic activities once informed of their local government's performance is relevant to decentralized governance. Applying propensity score matching technique on a unique household-level dataset from the Philippines, it is found that the knowledge of an index of local government performance has positive and statistically significant effects on the likelihood of membership in local organizations and participation in local projects. The estimated average treatment effects are robust to choice of comparison groups, matching algorithm and to possible effects of unobserved variables. Thus, transparency in local government activities can deepen citizenship.
Keywords: D83; H70; C21; 330